The Effects of DRTA Reading Technique on the Senior High School Students’ Reading Comprehension Achievement and Reading Behaviors - Maria Agatha Dinda Paskarini (Magister Scientiae, 2011)
This study was done to find out the effect of DR-TA to Senior High School students’ reading comprehension and also their reading behavior during the reading activity. In order to answer the problems formulated, the experiment was held, two classes were used. One class was the control class and another was the experiment class. The subjects of the study were students from Grade XI social program of Senior High School. The 50 students were chosen randomly. The treatment was given seven times. Before the treatment, a pretest was given to each group, and then after all of the treatment was given, a posttest was held. The score of the two tests was then processed by ANCOVA. The result of the data analysis showed that the two reading techniques gave different effects on students’ reading comprehension and reading behaviors. Based on the statistical analysis, the students who were taught by DR-TA showed higher reading comprehension achievement progress than the control group who were taught using ARAD. The result of the questioner and video observation showed that most of good reader behaviors were done by the experimental group while less of the control group did them. However, some of good reader behaviors were not done by most of both groups.